A theoretical and empirical investigation of the dual purpose funds - Ingersoll, Jonathan E. (Journal of Financial Economics, 1976)
Using the option pricing methods developed by Black and Scholes as a general technique for contingent claims analysis, this paper examines a class of mutual funds known as Dual Purpose Funds. By constructing a simplified model for these funds under the ‘perfect hedge’ conditions of Black and Scholes, it is demonstrated that the asset value of the fund will always exceed the market value and that it is not inconsistent with market equilibrium or efficiency for the capital shares to sell at a discount. The simple model predicts price fluctuations in the seven dual funds studied quite well; however, there is a persistent downward bias in the predicted price level. Finally, refinements to the model are examined to determine the nature of the misspecification causing this bias.